626.MYSTERY SHOPPERS AND NET PROMOTER SCORE TOOLS FOR CUSTOMER SATISFACTION IMPROVEMENT - Goce, Boceski; Gligorce, Vrtanoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
In conditions of high levels of globalization and strong competition, customer satisfaction is an essential prerequisite for their loyalty and successful retailing. Defining measurable parameters that affect customer satisfaction is a prerequisite for measuring and tracking them. The AIDA model is the basis of the sales funnel concept that allows defining and measuring the value conversions of one funnel element to another. Through an analysis of two case studies: a local retail chain and an international Toyota retail, both based on the AIDA model, adapted sales funnels and conversion indicators of the sales funnel elements are presented as a measure of the success of the retail chain. Two methodologies for creating customer satisfaction are analyzed: BIG 4 and AWOS, including the tools: Upsale and CrossSale to enhance it. In addition to the thesis on the importance of customer satisfaction and the power of its influence, surveys of local sales staff and views of top world managers are presented. The importance of feedback from customer to company is demonstrated through realistic values from the application of two tools: Mystery Shoppers MS, and Net Promoter Score NPS. The process of defining an adapted sales conversion funnel is presented which is practically applied through the analysis of two case studies. The cases demonstrate the importance of educating sales staff, as well as the impact of marketing and commercial campaigns on sales success. The conclusion of the research is that customer satisfaction is a prerequisite for successful retailing and a major competitive advantage that should be constantly in the focus of every successful company.